Cross-talk between human airway epithelial cells and 3T3-J2 feeder cells involves partial activation of human MET by murine HGF. - Robert E Hynds; Kate H C Gowers; Ersilia Nigro; Colin R Butler; Paola Bonfanti; Adam Giangreco; Cecilia M Prêle; Sam M Janes (PLoS ONE, 2018)
There is considerable interest in the ex vivo propagation of primary human basal epithelial stem/progenitor cells with a view to their use in drug development, toxicity testing and regenerative medicine. These cells can be expanded in co-culture with mitotically inactivated 3T3-J2 murine embryonic feeder cells but, similar to other epithelial cell culture systems employing 3T3-J2 cells, the aspects of cross-talk between 3T3-J2 cells and human airway basal cells that are critical for their expansion remain largely unknown. In this study, we investigated secreted growth factors that are produced by 3T3-J2 cells and act upon primary human airway basal cells. We found robust production of hepatocyte growth factor (HGF) from fibroblast feeder cells following mitotic inactivation. Consistent with the limited cross-species reactivity of murine HGF on the human HGF receptor (MET; HGFR), MET inhibition did not affect proliferative responses in human airway basal cells and HGF could not replace feeder cells in this culture system. However, we found that murine HGF is not completely inactive on human airway epithelial cells or cancer cell lines but stimulates the phosphorylation of GRB2-associated-binding protein 2 (GAB2) and signal transducer and activator of transcription 6 (STAT6). Although HGF induces phosphorylation of STAT6 tyrosine 641 (Y641), there is no subsequent STAT6 nuclear translocation or STAT6-driven transcriptional response. Overall, these findings highlight the relevance of cross-species protein interactions between murine feeder cells and human epithelial cells in 3T3-J2 co-culture and demonstrate that STAT6 phosphorylation occurs in response to MET activation in epithelial cells. However, STAT6 nuclear translocation does not occur in response to HGF, precluding the transcriptional activity of STAT6.